HIGH-TECH AKUPUNKTUR FÜR DIE PRÄVENTION VON LEBENSSTIL BEDINGTEN ERKRANKUNGEN — EINE „SINO-AUSTRIAN“ KOOPERATION — FORTSETZUNG: Ein Projektbericht (Studiendesign) zur Teleakupunktur mit Wuhan in COVID-19-Pandemie-Zeiten - Litscher, Gerhard (Akupunkt Aurikulomed, 2020)
This project within a successful Sino-Austrian cooperation on high-tech acupuncture between Hubei University of Chinese Medicine in Wuhan and Medical University of Graz deals with clinical transcontinental tele acupuncture measurements in healthy volunteers and patients with fatigue and stress. Heart rate (HR) and heart rate variability (HRV) measurements should be performed under standardized conditions in Wuhan, China, and the data analyses should be performed in Graz, Austria. Similar to previous measurements, the electrocardiograms should be recorded during acupuncture and/or moxibustion. The values during and after stimulation of total HRV, of the low-frequency (LF) and high-frequency (HF), and those of LF/HF ratio should be compared to baseline values and values of healthy volunteers. Together with the results of the preliminary study, the present results can serve as a solid basis for further development of acupuncture stimulation and moxibustion equipment for complementary use in treating fatigue and symptoms of stress. Both institutions have experts for this kind of experiments.